Preeclampsia is associated with failure of human cytotrophoblasts to mimic a vascular adhesion phenotype. One cause of defective endovascular invasion in this syndrome? - Zhou, Y. (American Society for Clinical Investigation, 1997)
In human pregnancy, placental cytotrophoblasts that invade the uterus downregulate the expression of adhesion receptors that are characteristic of their epithelial origin, and upregulate the expression of adhesion receptors that are expressed by vascular cells. We suggest that this transformation could be critical to endovascular invasion, the process whereby cytotrophoblasts invade the uterine spiral arterioles and line their walls (Zhou et al. J. Clin. Invest. 1997. 99: 2139-2151.). To better understand the in vivo significance of these findings, we tested the hypothesis that in preeclampsia, an important disease of pregnancy in which endovascular invasion is abrogated, cytotrophoblasts fail to adopt a vascular adhesion phenotype. In experiments described here we stained placental bed biopsy specimens from age-matched control pregnancies and from those complicated by preeclampsia with antibodies that recognize adhesion molecules that are normally modulated during this transformation. In preeclampsia, differentiating/invading cytotrophoblasts fail to express properly many of these molecules, including integrin, cadherin, and Ig superfamily members. These results suggest that preeclampsia is associated with failure of cytotrophoblasts to mimic a vascular adhesion phenotype. The functional consequences of this abnormality are unknown, but are likely to affect negatively cytotrophoblast endovascular invasion and uterine arteriole remodeling, thereby compromising blood flow to the maternal-fetal interface.